The Year of Study and the Physical Activity of Students of Selected Fields of Study at the State School of Higher Education in Biała Podlaska - Barbara Bergier; Józef Bergier; Ewelina Niźnikowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The aim of the study was to analyze the level of physical activity of students of selected fields of study at Biała Podlaska University depending on the year of study. The study involved 450 people, studying at the first and second stages of education at the State School of Higher Education (PSW) in Biała Podlaska. In the study, a method of diagnostic survey was applied, with the use of the International Physical Activity Questionnaire IPAQ - short version. Based on the analysis it was concluded that the surveyed students were characterized by a moderate level of physical activity. The diversity of types of physical activity of students in relation to the year of study were statistically significant in terms of total activity, moderate activity and walking - in favor of students of the second year of undergraduate studies.